A Study on the Application of Digital Twin Technology in Manufacturing Operations at Indo Rama Synthetics - Shirsat, Elesh Uddhav; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
Digital Twin Technology (DTT) has emerged as a transformative innovation in modern manufacturing, enabling real-time data integration and operational optimization. This study explores the implementation of Digital Twin Technology within the manufacturing operations of Indo Rama Synthetics, focusing on its potential to enhance efficiency, reduce downtime, and improve decision-making processes. The research examines how DTT creates a virtual replica of physical systems to monitor, simulate, and predict performance, offering a proactive approach to managing manufacturing workflows. Through a blend of quantitative and qualitative methodologies, the study evaluates key parameters such as system adaptability, predictive maintenance efficacy, and overall operational enhancements achieved through DTT deployment. Results highlight significant improvements in resource allocation, production timelines, and cost reduction, underlining the strategic value of digital twins in the competitive manufacturing landscape. Challenges such as implementation costs and integration complexities are also addressed, providing a balanced perspective on adopting this technology. By offering insights into the practical application of DTT at Indo Rama Synthetics, the study contributes to the broader discourse on digital transformation in manufacturing, setting a foundation for future explorations in this domain.